Porous film, and production method of porous film

JP2025023566APending Publication Date: 2025-02-17CHUKOH CHEM IND LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023127825
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、コシが強く、通気性および耐水圧にも優れる多孔質フィルムを安定的に提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023566000001_ABST
    Figure 2025023566000001_ABST
Patent Text Reader

Abstract

To provide a porous film which has strong stiffness and is excellent in air permeability and in water pressure resistance.SOLUTION: Provided is a porous film comprising fluororesin. The porous film has a mean value of Gurley air permeability of 20 seconds or less, and water pressure resistance of 100 kPa or more, and a value of [(mean value of bending resistance)-(standard deviation of bending resistance)×3] of 17 mm or more.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous film and a method for producing a porous film. [Background technology]

[0002] In automotive electrical components, OA (office automation) equipment, home appliances, medical equipment, etc., waterproof breathable filters are used to eliminate the pressure difference between the inside and outside of a housing that houses electronic components and control boards, etc. This waterproof breathable filter is attached to the housing so as to cover an opening provided in the housing, and is dustproof and waterproof while ensuring ventilation. Polytetrafluoroethylene (PTFE) porous film is often used as the waterproof breathable filter.

[0003] In addition, bag-in-boxes, which combine a cardboard box-based exterior with a plastic inner bag, are used to transport and store large amounts of liquid. When unused, the exterior and inner bag can be separated and folded up separately, which saves space during storage and makes disposal easy, so bag-in-boxes are widely used as commercial liquid containers. Examples of liquids that can be stored in bag-in-boxes include beverages such as drinking water, foods such as seasonings, alcoholic beverages, and industrial chemicals such as developing solutions, liquid fertilizers, and adhesives. A cap equipped with a porous film for adjusting the internal pressure is used for the inner bag of the bag-in-box. Since the contents of the inner bag of the bag-in-box are liquid, the porous film of the cap is required to have breathability for adjusting the internal pressure and a function to prevent foreign objects from entering from the outside, as well as water pressure resistance to prevent the stored liquid from leaking.

[0004] The stiffness of a PTFE porous film tends to weaken as the porosity increases due to stretching. Therefore, the porosity of a biaxially stretched product is higher than that of a uniaxially stretched product. Furthermore, the thickness also rapidly decreases during stretching in the width direction, so the stiffness of a biaxially stretched product tends to be extremely weaker than that of a uniaxially stretched product. However, a biaxially stretched product has a better balance of breathability and water pressure resistance than a uniaxially stretched product. In detail, breathability and water pressure resistance are in a trade-off relationship, but a biaxially stretched product has a sufficient margin in the usable range for both breathability and water pressure resistance, and the range in which both can be achieved while remaining within the usable range is wide, so it can be said that the balance between the two is good. Therefore, a biaxially stretched product can achieve both breathability and water pressure resistance, which cannot be achieved by a uniaxially stretched product. Therefore, biaxially stretched products are widely used in vent filters (internal pressure adjustment) and the like by laminating them with nonwoven fabrics, meshes, etc. to improve handling.

[0005] However, in areas where chemical resistance is required for PTFE porous film applications, laminated products cannot be used, and double-sided tape cannot be used for processing, so the film is joined by heat welding. In this way, PTFE porous film alone may be required. In such cases, biaxially stretched products have poor stiffness and are difficult to handle. For example, Patent Document 1 (JP 2021-195404 A) discloses a PTFE porous film that has excellent handling properties even when used alone. Specifically, a porous film that is stiff and has excellent breathability is described. In Patent Document 1, in order to obtain a porous film that is both stiff and breathable, an unsintered PTFE sheet is uniaxially stretched, and then a process of shrinking the porous film is performed and then fired (sintered). According to Patent Document 1, biaxial stretching may reduce the thickness and reduce the stiffness, so it is preferable to only perform uniaxial stretching in order to maintain strong stiffness. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2021-195404 Summary of the Invention [Problem to be solved by the invention]

[0007] The object of the present invention is to provide a porous film having a high stiffness and excellent breathability and water pressure resistance. [Means for solving the problem]

[0008] A porous film containing a fluororesin is provided, which has an average Gurley air permeability of 20 seconds or less, a water pressure resistance of 100 kPa or more, and a bending resistance (average value - standard deviation x 3) of 17 mm or more.

[0009] Also provided is a method for producing a porous film, which includes preparing an unsintered tape containing a fluororesin, uniaxially stretching the unsintered tape in a first direction to obtain a uniaxially oriented tape, stretching the uniaxially oriented tape in a second direction intersecting the first direction to obtain a biaxially oriented tape, and stretching the biaxially oriented tape in the first direction. Effect of the Invention

[0010] According to the present invention, it is possible to stably provide a porous film that is strong in stiffness and has excellent breathability and water pressure resistance. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a perspective view showing a schematic diagram of an example of a roll including a porous film according to the present invention. [Diagram 2] FIG. 1 is a conceptual diagram showing the application of a conventional porous film to pick-up by an automated machine. [Diagram 3] FIG. 2 is a conceptual diagram showing the application of the porous film according to the present invention to pick-up by an automated machine. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The porous film for venting (adjusting internal pressure) the cap of a bag-in-box is, for example, heat-sealed to the cap. Conventionally, for example, the porous film is supplied in a sheet-fed manner using a micro-adhesive tape as a separator, and during welding processing, it is manually picked up one by one with a tool such as tweezers, placed on the welding part of the cap, and then welded by a welding machine. In order to automate the process from picking up the film to heat sealing, the pickup of the supplied porous film by an automatic machine has been considered.

[0013] In order to enable pick-up by an automatic machine, stiffness is required. For example, a typical biaxially stretched film does not have stiffness, so it cannot be picked up by an automatic machine. A uniaxially stretched film has stronger stiffness and can be used for pick-up by an automatic machine. However, it is difficult to balance breathability and water pressure resistance with a uniaxially stretched product, and it can only meet a small part of the performance required for a vent. In addition, since a uniaxially stretched product is easily stretched in the width direction, it stretches in the width direction during welding, increasing the amount of air permeability and decreasing the water pressure resistance, and there is a tendency for the properties to change significantly before and after welding. Therefore, the present invention was discovered as a result of studying how to improve the stiffness of a biaxially stretched product in order to widely meet the required properties.

[0014] According to the present invention, there is provided a porous film containing a fluororesin. The porous film has an average Gurley air permeability of 20 seconds or less, a water pressure resistance of 100 kPa or more, and a bending resistance of 17 mm or more. Here, a bending resistance of 17 mm or more is a value obtained by subtracting three times the standard deviation from the average value on the film surface ([(average bending resistance)-(standard deviation of bending resistance×3)]≧17 mm), that is, is statistically shown over almost the entire film surface (99.7% or more).

[0015] The porous film is, for example, a film having a porous structure and containing a fluororesin. The fluororesin preferably contains polytetrafluoroethylene (PTFE). The porous film may be made of, for example, only PTFE.

[0016] Biaxially stretched PTFE membranes have a high porosity, so conventional membranes have a low bending resistance. The bending resistance can be increased by setting a low stretch ratio to reduce the porosity, but in that case the breathability decreases (Gurley air permeability increases). Thus, there is a trade-off between breathability and bending resistance, but if the breathability is 20 seconds or less and the bending resistance is 17 mm or more, it can exhibit both the function of adjusting the internal pressure and the stiffness suitable for pick-up by an automatic machine. It is more preferable that the breathability is 15 seconds or less.

[0017] In addition, biaxially stretched products have a better balance between breathability and water pressure resistance than uniaxially stretched products. The porous film is a biaxially stretched film, and exhibits a water pressure resistance of 100 kPa or more while exhibiting a breathability of 20 seconds or less. Therefore, it can be suitably used for bag-in-box vents.

[0018] A uniaxially stretched fluororesin product is typically obtained by uniaxially stretching a fluororesin sheet or tape in an unbaked state in the machine direction (MD) and then baking it. A conventional biaxially stretched fluororesin product is typically obtained by further stretching in the transverse direction (TD) perpendicular to the MD direction after the uniaxial stretching and then baking it. The above-mentioned porous film with an air permeability of 20 seconds or less, a water pressure resistance of 100 kPa or more, and a bending resistance of 17 mm or more can be obtained by stretching in the TD direction and then stretching in the MD direction again. The stiffness is significantly increased by stretching in the MD direction again, and a porous film having the properties of a biaxially stretched product and strong stiffness can be obtained.

[0019] The porous film has a stiffness (bending resistance) that allows it to be picked up by an automatic machine. Since the film is compatible with an automatic machine, it is more preferable to adopt a roll-type supply form rather than a sheet-type supply form from the viewpoint of automating the production site to which the film is applied. The porous film can be used in the form of a roll shown in FIG. 1, for example, in a production line for products that use the porous film.

[0020] The roll 10 shown in Fig. 1 includes a plurality of porous films 1 and a separator 2 on which the plurality of porous films 1 are arranged. The separator 2 is spirally wound around a core material 3 with the porous films 1 arranged on the inner surface side. Fig. 1 shows a state in which the separator 2 on which the porous films 1 are placed is partially unwound.

[0021] The porous film 1 is a film containing the above-mentioned fluororesin with an air permeability of 20 seconds or less, a water pressure resistance of 100 kPa or more, and a bending resistance of 17 mm or more. The porous film 1 has a shape and dimensions according to the product in which it is incorporated. For example, a film for a vent of a cap of a bag-in-box can be a circular membrane with a diameter of 20 mm. The separator 2 is, for example, a micro-adhesive tape.

[0022] As mentioned above, biaxially stretched films are suitable for applications such as bag-in-box vents that require both breathability and water pressure resistance, but conventional biaxially stretched films have low stiffness. Therefore, conventional biaxially stretched films are not suitable for pick-up by automatic machines. This will be explained with reference to Figure 2.

[0023] FIG. 2 shows a conceptual diagram of a conventional porous film applied to pick-up by an automatic machine. The separator 2 with the porous film 11 on its upper surface is conveyed in the flow direction 100, folded along the edge of the front support plate 21 of the two support plates 21, and passed through the gap between the support plates 21. The support plate 21 is made of, for example, stainless steel. With a porous film 11 that is weak in stiffness, even if the separator 2 on which the film is placed is folded, the porous film 11 does not float from the separator 2, and the porous film 11 itself also bends and follows the separator 2. Since the porous film 11 does not float, for example, the porous film 11 cannot be picked up by a suction pad 22 that sucks air from a tube 23 to adsorb an object. In this way, automation is difficult when using a conventional biaxially stretched film with weak stiffness.

[0024] A porous film with a bending resistance of 17 mm or more has enough stiffness to be lifted off the separator, which in turn makes it possible to automate the pickup. This will be explained with reference to Figure 3.

[0025] FIG. 3 shows a conceptual diagram showing the case where the porous film according to the present invention is applied to pick-up by an automatic machine. FIG. 3 shows the same state as FIG. 2, except that the porous film 11, which is a conventional biaxially stretched product with weak stiffness, is replaced with the porous film 1 of the present invention with strong stiffness. The separator 2 carrying the porous film 1 conveyed in the flow direction 100 may be, for example, that supplied from the roll 10 shown in FIG. 1. When the separator 2 is folded along the edge of the support plate 21 at the front, the porous film 1 placed on the folded part may partially float from the separator 2, and only the porous film 1 may protrude above the support plate 21 at the back side. In this way, the porous film 1 can be peeled off simply by folding the separator 2, and the peeled porous film 1 can be picked up by, for example, the suction pad 22. The picked-up porous film 1 is transported, and is released from the suction pad 22 by stopping the suction by the tube 23 or supplying gas from the tube 23 to the suction pad, and placed on the object to be welded. In this way, if the porous film 1 is stiff, it can be applied to automatic pick-up.

[0026] Usually, uniaxially stretched products are thick and have high bending resistance. Conventional biaxially stretched products are thin and have low bending resistance. Uniaxially stretched products that meet the conditions of the air permeability required for a breathable membrane rarely achieve a water pressure resistance of 90 kPa or more. For example, if the required air permeability for a uniaxially stretched product is around 10 seconds, the water pressure resistance will be 80 kPa or less, and it is almost impossible to manufacture a water pressure resistance of 100 kPa or more unless the air permeability is reduced. An example of a good balance between air permeability and water pressure resistance for a uniaxially stretched product is an air permeability of 10 seconds and a water pressure resistance of around 70 kPa. In this case, the water pressure resistance that can be guaranteed for the uniaxially stretched product from the perspective of manufacturing stability is only about 50 kPa.

[0027] With biaxially stretched products, water pressure resistance of 100 kPa or more can be easily achieved. In one example of a biaxially stretched product, the air permeability is 9 to 15 seconds, and the water pressure resistance is 120 to 170 kPa. However, while the water pressure resistance is high with conventional biaxial stretching alone, the bending resistance is extremely low. However, if there is no limit on the bending resistance, it is easy to achieve 100 kPa or more in 1 second or less.

[0028] The porous film according to the present invention can stably achieve a water pressure resistance of 100 kPa or more while having a high bending resistance.

[0029] The porous film has a thickness of, for example, 0.10 mm or more and 0.16 mm or less. The porous film is an improvement on the conventional biaxially stretched product, and is thinner than the uniaxially stretched product. The thickness is more preferably 0.12 mm or more and 0.14 mm or less.

[0030] A method for producing a porous film includes preparing an unsintered tape containing a fluororesin, uniaxially stretching the unsintered tape in a first direction to obtain a uniaxially oriented tape, stretching the uniaxially oriented tape in a second direction intersecting the first direction to obtain a biaxially oriented tape, and stretching the biaxially oriented tape in the first direction.

[0031] The green tape can be prepared, for example, as follows.

[0032] A fine powder containing fluororesin is prepared, and 100 parts by mass of this powder are mixed with, for example, 20 to 30 parts by mass of hydrocarbon oil as an auxiliary. For example, fine powders with an average particle size of 250 μm to 800 μm can be used. The average particle size is the particle size D that corresponds to 50% of the total number of particles in the particle size distribution measured based on the laser diffraction scattering method. 50 means...

[0033] The mixture is stirred to be homogenous, and then the paste is extruded and preformed, for example, into a sheet. The preform obtained is rolled, for example, using a metal roll. The auxiliary is then removed to obtain an unsintered fluororesin tape. The thickness of the unsintered fluororesin tape is, for example, within the range of 50 μm to 600 μm.

[0034] The unsintered tape is uniaxially stretched in the first direction to obtain a uniaxially stretched tape, for example, under the following conditions. The unsintered tape is stretched in the first direction at a temperature below the melting point by a factor of 2 to 6. Here, the first direction is, for example, the direction in which the unsintered tape was rolled in preparation, that is, the MD direction. This stretching at a temperature below the melting point draws out fibrils (fibers) between the nodes (resin lumps) of the fluororesin. As a result, cavities are formed in the resin tape, making it porous.

[0035] The uniaxially stretched tape is stretched in a second direction intersecting the first direction to obtain a biaxially stretched tape, for example, under the following conditions: The uniaxially stretched tape obtained by the above uniaxial stretching is stretched in the second direction at a temperature below the melting point at a ratio of 2 to 6 times. The second direction is, for example, a direction perpendicular to the first direction, i.e., the TD direction. This stretching in the second axis further splits the nodes after uniaxial stretching.

[0036] Stretching the biaxially oriented tape in the first direction, i.e., uniaxial re-stretching, is carried out, for example, under the following conditions: The biaxially oriented tape obtained by stretching in the second direction is stretched in the first direction at a ratio of 1.1 to 2 times at a temperature below the melting point. By stretching in the first direction again, the fibrils are aligned in the first direction, and the effect of suppressing the decrease in bending resistance is obtained.

[0037] It is preferable to bake the uniaxially stretched tape before stretching in the second direction. Although baking causes node splitting during stretching in the second direction, unlike conventional biaxial stretching, it prevents fibrils from being pulled out from the nodes in the TD direction, and does not result in fine nodes. This reduces the reduction in thickness due to stretching, and suppresses the decrease in bending resistance. In addition, after stretching in the second direction, heat setting by heating at a temperature equal to or higher than the melting point of the fluororesin may be performed before stretching again in the first direction.

[0038] In conventional uniaxially stretched products, the nodes are large, the fibrils pulled out from the nodes are thick, and these thick fibrils are aligned in the length direction. In conventional biaxially stretched products, fibrils are further pulled out from the nodes after uniaxial stretching when stretched to the second axis, and the thick nodes generated during uniaxial stretching are also finely split and thinned. For this reason, in conventional biaxially stretched products, the nodes are small and the fibrils are not thin and aligned, so the bending resistance is extremely low compared to uniaxially stretched products.

[0039] The band-shaped (tape-shaped) porous film obtained by performing a total of three stretching operations may be appropriately cut or punched into a shape according to the intended use.

[0040] The bending resistance is measured by a method conforming to the 45° cantilever method (JIS L 1096:2010 A method) using a sample obtained by cutting the film. A strip-shaped test piece of 25 mm x approximately 150 mm is used as the sample, and a bending resistance tester CAN-1MCC manufactured by Daiei Kagaku Seiki Seisakusho Co., Ltd. or a device having equivalent functions is used as the device. Multiple samples are taken from the film before cutting, and the average value and standard deviation are calculated from the bending resistance measurement results.

[0041] The Gurley air permeability of the porous film can be measured according to the Gurley tester method (JIS P 8117:2009). For example, an automatic Gurley densometer manufactured by Yasuda Seiki Seisakusho Co., Ltd., or an apparatus having equivalent functions can be used as the apparatus used to measure the Gurley air permeability. The test piece is prepared in the same manner as in the 45° cantilever method. A number of samples are taken from the film before cutting, and the average value is calculated from the results of the air permeability measurement.

[0042] The water pressure resistance of the porous film is determined by a water pressure resistance test conforming to the B method (high water pressure method) of JIS L 1092:2009. The jig used is a φ3 mm plate specified in JIS K 6404-3:2020. The test piece is prepared in the same manner as the 45° cantilever method described above. EXAMPLES

[0043] Examples will be described below, but the embodiments of the present invention are not limited to the examples described below.

[0044] <Preparation of porous film> (Example) Step 1: Preparation of green tape (rolling and drying of paste extrusion) PTFE fine powder (F-104 manufactured by Daikin Industries, Ltd.) was mixed uniformly with 25 parts by mass of hydrocarbon oil (ISOPAR M manufactured by ExxonMobil Corp.) as an extrusion aid. This mixture was paste-extruded and preformed into a sheet. This preform was passed between a pair of metal rolling rolls and further dried to remove the aid, and a rectangular unsintered tape with a thickness of 0.3 mm and a width of 180 mm was obtained.

[0045] Step 2: Uniaxial stretching (MD direction) of unsintered tape and sintering The resulting unsintered tape was stretched (uniaxially stretched) 2.1 times in the machine direction (MD) at 200° C. using a roll stretching machine. The resulting uniaxially stretched tape was further sintered at 360° C. to obtain a sintered tape with a thickness of 0.2 mm and a width of 150 mm.

[0046] Step 3: Widening and stretching the fired tape (TD direction) Both ends of this fired tape were held by a tenter and stretched 3 times in the transverse direction (TD) at 200° C. After further heat setting at 370° C., the gripped portions were trimmed to obtain a biaxially stretched tape with a thickness of 0.14 mm and a width of 310 mm.

[0047] Step 4: Re-stretching the biaxially oriented tape in the MD direction This biaxially stretched tape was stretched 1.2 times in the machine direction (MD) at 250° C. using a roll stretching machine to obtain a tape-like porous film having a thickness of 0.14 mm and a width of 230 mm.

[0048] Comparative Example 1 A tape-shaped porous film was obtained in the same manner as in Example 1, except that step 4 was omitted.

[0049] Comparative Example 2 Step 1: Preparation of green tape (rolling and drying of paste extrusion) PTFE fine powder (6J, ​​manufactured by Mitsui Chemours Fluoro Products) was mixed uniformly with 26 parts by mass of hydrocarbon oil (Isopar M, manufactured by Exxon Mobil Corp.) as an extrusion aid. This mixture was paste-extruded and preformed into a sheet. This preform was passed between a pair of metal rolling rolls and further dried to remove the aid, yielding a rectangular unsintered tape with a thickness of 0.24 mm and a width of 160 mm.

[0050] Step 2: Uniaxial stretching (MD direction) of unsintered tape and sintering The resulting unsintered tape was stretched 2.1 times in the machine direction (MD) at 280° C. using a roll stretching machine, and then sintered at 360° C. to obtain a sintered tape (porous film) with a thickness of 0.2 mm and a width of 130 mm.

[0051] Comparative Example 3 Step 1: Preparation of green tape (rolling and drying of paste extrusion) PTFE fine powder (F-104 manufactured by Daikin Industries, Ltd.) was mixed uniformly with 25 parts by mass of hydrocarbon oil (ISOPAR M manufactured by ExxonMobil Corp.) as an extrusion aid. This mixture was extruded into a paste and preformed into a rod shape. This preform was passed between a pair of metal rolling rolls and further dried to remove the aid, and a rectangular unsintered tape with a thickness of 0.34 mm and a width of 185 mm was obtained.

[0052] Step 2: Uniaxial stretching of unsintered tape (MD direction) The obtained unsintered tape was stretched 5 times (uniaxially stretched) in the machine direction (MD) at 250° C. using a roll stretching machine. The tape payout speed was 2.5 m / min.

[0053] Step 3: Shrinking step The obtained uniaxially stretched tape was conveyed in a deflected state so as to pass between two pairs of heated rolls, both of which were heated to 250° C. The tape was unwound at a speed of 2.5 m / min. In this manner, a shrink tape having a thickness of 0.31 mm was obtained by shrinking the tape at a shrinkage rate of 20%.

[0054] Step 4: Firing This shrink tape was fired at 380° C. while being conveyed at a payout speed of 3 m / min. The fired tape was stretched 1.11 times to obtain a fired tape (porous film) having a thickness of 0.28 mm.

[0055] Comparative Example 4 A tape-shaped porous film was obtained in the same manner as in Comparative Example 3, except that after step 2 of uniaxially stretching in the MD direction, stretching in the TD direction was performed before step 3 of shrinking.

[0056] <Evaluation> The porous films produced in the Examples and Comparative Examples were measured according to the 45° cantilever method (JIS L 1096:2010, Method A) using the procedure described above. For the Examples and Comparative Example 1, measurements were made at 8 points in the width direction and 11 points in the length direction (88 points in total). For Comparative Example 2, measurements were made at 4 points in the width direction and 3 points in the length direction (12 points in total). For Comparative Example 3, measurements were made at 4 points in the width direction and 6 points in the length direction (24 points in total). In addition, the bending hardness was calculated from the bending resistance (bending length) and basis weight of each film: bending hardness (mNcm) = [basis weight] x [bending length] 3 ×10 -3 However, for Comparative Example 4, the bending resistance of the film was so low that it could not be measured. Specifically, when the sampled test piece was slid from the horizontal stand to the 45° inclined plane, the test piece buckled and could not be slid. Since it was impossible to measure the bending resistance, other measurements and tests were omitted for Comparative Example 4. The bending resistance at each measurement point obtained for each of the examples and Comparative Examples 1 to 3 are shown in Tables 1 to 4 below. Also shown are the average value and standard deviation of the bending resistance (bending length), and the bending hardness.

[0057] [Table 1]

[0058] [Table 2]

[0059] [Table 3]

[0060] [Table 4]

[0061] In addition, the porous films produced in each example were measured according to the Gurley tester method (JIS P 8177:2009) using the procedure described above. For the examples, measurements were taken at three points in the width direction and 11 points in the length direction (total of 33 points). For Comparative Example 1, measurements were taken at five points in the width direction and 11 points in the length direction (total of 55 points). For Comparative Example 2, measurements were taken at two points in the width direction and five points in the length direction (total of 10 points). For Comparative Example 3, measurements were taken at four points in the width direction and three points in the length direction (total of 12 points). The following Tables 5 to 8 show the Gurley air permeability at each measurement point obtained for each of the examples and Comparative Examples 1 to 3. The average air permeability and the standard deviation are also shown.

[0062] [Table 5]

[0063] [Table 6]

[0064] [Table 7]

[0065] [Table 8]

[0066] Furthermore, the porous films produced in each example were subjected to a water pressure resistance test in accordance with the JIS L 1092:2009 B method (high water pressure method) test, using the procedure described above. For the examples, measurements were taken at one point in the width direction and 11 points in the length direction (11 points in total). For comparative example 1, measurements were taken at two points in the width direction and 11 points in the length direction (22 points in total). For comparative example 2, measurements were taken at one point in the width direction and 5 points in the length direction (5 points in total). For comparative example 3, measurements were taken at two points in the width direction and 3 points in the length direction (6 points in total). The following Tables 9 to 12 show the water pressure resistance at each measurement point obtained for each of the examples and comparative examples 1 to 3. The average water pressure resistance and the standard deviation are also shown.

[0067] [Table 9]

[0068] [Table 10]

[0069] [Table 11]

[0070] [Table 12]

[0071] <Automatic machine pick-up test> The results of the evaluation test of bending resistance applicable to pick-up by an automatic machine are shown below. For samples A to C used in the test, the average, minimum, and maximum bending resistance of the tape before cutting out the test pieces, as well as whether each test piece could be picked up automatically when using the automatic machine, are shown in Table 13 below.

[0072] [Table 13]

[0073] As shown in Table 13, the porous film having a bending resistance of 17 mm or more could be picked up by an automatic machine. As shown in Table 1, the porous film according to the embodiment statistically had a bending resistance of 20.8 mm or more throughout (99.7% or more: average value-standard deviation x 3), and it can be seen that a bending resistance of 17 mm or more was stably obtained. In addition, the porous film according to the embodiment also had good breathability (average Gurley air permeability of 14.5 sec) and high water pressure resistance (average 141 kPa) (Tables 5 and 9). In contrast, in any of Comparative Examples 1 to 3, a film having a stable high bending resistance (average value-standard deviation x 3≧17 mm), high breathability (average Gurley air permeability of 15 sec or less), and high water pressure resistance (100 kPa or more) was not obtained.

[0074] The present invention is not limited to the above-mentioned embodiment, and can be modified in various ways without departing from the gist of the present invention. The embodiments may be combined as appropriate, and in that case, the combined effect can be obtained. Furthermore, the above-mentioned embodiment includes various inventions, and various inventions can be extracted by combinations selected from the multiple components disclosed. For example, if the problem can be solved and the effect can be obtained even if some components are deleted from all the components shown in the embodiment, the configuration from which the components are deleted can be extracted as an invention. [Explanation of symbols]

[0075] 1...porous film, 2...separator, 3...core material, 10...roll, 11...porous film, 21...support plate, 22...suction pad, 23...tube.

Claims

1. Contains fluororesin, A porous film having an average Gurley air permeability of 20 seconds or less, a water pressure resistance of 100 kPa or more, and a bending resistance (average value-standard deviation x 3) of 17 mm or more.

2. The porous film of claim 1 having a thickness of 0.10 mm or more and 0.16 mm or less.

3. The porous film according to claim 1 or 2, wherein the fluororesin comprises polytetrafluoroethylene.

4. Providing an unfired tape including a fluororesin; uniaxially stretching the green tape in a first direction to obtain a uniaxially stretched tape; stretching the uniaxially oriented tape in a second direction intersecting the first direction to obtain a biaxially oriented tape; stretching the biaxially oriented tape in the first direction. A method for producing a porous film.

5. The method of claim 4 further comprising sintering the uniaxially stretched tape prior to stretching in the second direction.

Citation Information

Patent Citations

  • Porous film and method for producing porous film

    JP2021195404A